O dinamismo na associação peixe-planta : variações ontogênicas em alguns atributos da assembleia em lagoas de uma planície de inundação Neotropical. - Iquematsu, Marcia Sayuri (2017)
With the principle that as aquatic macrophytes increase the structural complexity of the habitat, it is proposed the hypothesis that this complexity increases the diversity, an abundance and an occurrence of fish species in different degrees of ontogenic development. It was collected monthly during February 2011 to February 2012, in two lagoons, one being permanently connected with Ivinheima River and the other periodically connected to this river. Six random samples were taken at each site, three in areas with of development, the highest values of fish richness and richness a macrophyte bank and three in open areas. The obtained results demonstrate that, regardless of the period were found at sites with macrophytes. A composition of the species for adult fish were correlated with changes in aquatic macrophyte species. Cyclic changes in the abundance, richness and composition of fish species as significant. The results indicate that habitat complexity exerts a structuring role on a fish community, regardless of the degree of ontogenic development of the organisms.